Matplotlib 2.x By Example - Yu, Allen (Packt Publishing Limited, 2017)
bUnlock deeper insights into visualization in form of 2D and 3D graphs using Matplotlib 2.x/bh2About This Book/h2ulliCreate and customize live graphs, by adding style, color, font to make appealing graphs./liliA complete guide with insightful use cases and examples to perform data visualizations with Matplotlib's extensive toolkits./liliCreate timestamp data visualizations on 2D and 3D graphs in form of plots, histogram, bar charts, scatterplots and more./li/ulh2Who This Book Is For/h2This book is for anyone interested in data visualization, to get insights from big data with Python and Matplotlib 2.x. With this book you will be able to extend your knowledge and learn how to use python code in order to visualize your data with Matplotlib.